Influence of early social environment on behavioural development and on later maternal behaviour of protein deprived rats - Franková, S (Activitas nervosa superior, 1981)
Female rats were subjected to protein deprivation (PD) by providing a low protein diet during the lactating period. Control (CO) females were fed on a well balanced diet. To part of the CO and PD litters, a virgin adult female - "the aunt" (A) was added to spend the light period of the day in these rearing cages. At weaning the PD pups were changed to extreme low protein diet and maintained on this régime until Day 49, then rehabilitated with the CO diet. The aunts continued visiting the PDA and COA groups until Day 49. - In the course of the suckling period, growth was recorded, individual and social activities were observed as well as mother-infant interactions in a novel environment. In the adult age, exploratory activity of females and contacts with both alien and own pups were tested. - It appeared that early PD suppressed growth, reduced exploratory activity of the pups and the number of active contacts with the mother and the littermates. The PD pups reared both by the mother and the aunt were in all behavioural tests superior to animals reared without the aunts, moreover, they did not differ from the CO group. Effect of aunt-rearing on the COA pups was less marked than on the PDA pups. - The test of exploratory activity in the adult age did not reveal effects of the early rearing. On the other hand, marked differences among groups were observed in tests of maternal behaviour. The early experience with the aunt resulted in an elevated frequency of contacts with pups in the PDA groups and it affected positively all indices of maternal behaviour.
Keywords: Behavior, Animal; Social Behavior; dietní proteiny; mateřské chování; Body Weight; Maternal Behavior; krysa rodu Rattus; Social Environment; Exploratory Behavior; Animals; ženské pohlaví; zvířata; Rats; chování zvířat; sociální chování; sociální prostředí; Female; tělesná hmotnost; Dietary Proteins; pátrací chování